1986
DOI: 10.1002/aja.1001770208
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and submicroscopic anatomy of the parabronchi, air sacs, and respiratory space of the budgerigar (Melopsittacus undulatus)

Abstract: The normal microscopic and submicroscopic structure of the lower respiratory tract of the budgerigar (Melopsittacus undulatus) is described and compared with other birds and mammals. Granular (type II) pneumocytes are confined to linings of air sacs, parabronchi, and their atria; however, their secretions (surfactant) cover the surfaces of the infundibula and respiratory space. Infundibula extend from the atria and give rise to the air capillaries, which branch and anastomose freely with those of adjacent infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
(39 reference statements)
3
6
0
Order By: Relevance
“…Only Abdalla and King (1975) point out the existence of a fifth dorsal furrow. The histological structure of the different bronchial types is basically in agreement with other previous studies (Chandra and Bharadwaj, 1971;Fernandez et al, 1972;Lopez et al, 1983Lopez et al, , 1986Smith et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Only Abdalla and King (1975) point out the existence of a fifth dorsal furrow. The histological structure of the different bronchial types is basically in agreement with other previous studies (Chandra and Bharadwaj, 1971;Fernandez et al, 1972;Lopez et al, 1983Lopez et al, , 1986Smith et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Breathing frequency and, consequently, the frequency of oscillatory surface area changes is much higher in mice ( 100 to 250 breaths per minute ) compared to larger mammals like pig and man ( 8 to 18 per minute ) [ 33,34] . Interestingly, surfactant from avian lungs, which contain so-called ''air capillaries'' instead of alveoli and are ven tilated without cyclic changes of the gas-exchanging surface area [ 35,36] , only contain minute amounts of PC16:0/14:0 and PC16:0/16:1 ( unpublished data ). Hence, PC16:0/14:0 and PC16:0/16:1 may be important components for the dyn amics of mammalian surfactant, although their precise alveolar function has not been investigated in detail.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, there is considerable controversy concerning the configuration of the avian respiratory epithelium and of the ultrastructure of the different epithelial cell types. The morphological similarity between the granular atrial cells in bird species with type II pneumocytes of the mammalian lung has been reported (Tyler and Pangborn, 1964;Lambson and Cohn, 1968;Akester, 1970;Smith et al, 1986). These authors suggested that the osmiophilic lamellar bodies are related to the production of the avian acellular lining layer covering not only the walls of the atria but also the surface of the infundibula and air capillaries.…”
mentioning
confidence: 89%